Assessment on the Status, Challenges and Prospects of Agricultural Technologies Intellectual Property Protection in Ethiopia - Kebede , Nahom M. (Journal of Sustainable Development Law and Policy, 2025)
Intellectual property right (IPR) is a broad term which describes the protections granted to the creators of IP, and includes; trademarks, copy right, patents, industrial designs, plant breeder’s right and in some jurisdictions trade secrets. The objective of this review is to show the status, challenges, and opportunities for agricultural technologies intellectual protection in the Ethiopian intellectual property regime. There are many agricultural technologies that have the potential to be protected by intellectual property. The results of this review article shows that there are several challenges for the protection of agricultural technologies IPR, including lack of awareness on the concept of IP, lack of clear policy direction for the protection of plant varieties, absence of IP assets creation mechanism, low level of institutional linkage among stakeholders, agricultural IPRs are complex in nature, poor organizational structure to register, and lack of experienced and well-qualified IP officials. But there are also prospects for agricultural technologies IPR protection. Some legal frameworks are in the process of revision, an independent authority for the agriculture sector has established, the Ministry of Agriculture has prepared the draft regulation for PBRs proclamation, amendment of the agricultural and rural development policy has in the process, and the country’s WTO accession process shows some improvement. In conclusion, the status of IP protection for agricultural technologies has not been well-developed and the registration of agricultural technologies is still null.